AFFLICTIONS UPON THE GREAT (TAMADDUN NURI JURNALI, 2025)
The article analyzes the interrelated and harmonious aspects of family environment, personal decline, and crises in socio-spiritual life based on the life of Amir Timur, the great conqueror, and his descendants.